Social Marketing and CSR: A Descriptive study in Nepal (TUTA Journal, 2022)
Nepal is amongst the lagers in context to adaptation of new technology and philosophy. Enterprises need to understand its core competencies and accordingly design and invest in social events. It is still an orthodox thought that only non-profitable entity organizes social events. This spherical concept has its strategic pro and cons. Nepalese brands are interchangeably using the social marketing as CSR and are not attached to their daily routines and duties. Different magnitude of organization have differ prospective initiation to social events.